Challenges and Promises of Radiomics for Rectal Cancer - Moreira, José Maria (2019)
Moreira, J. M., Santiago, I., Santinha, J., Figueiredo, N., Marias, K., Figueiredo, M., ... Papanikolaou, N. (2019). Challenges and Promises of Radiomics for Rectal Cancer. Current Colorectal Cancer Reports, 15(6), 175-180. https://doi.org/10.1007/s11888-019-00446-y